The effects of body mass on optimal load for power during resistance training - Soriano-Rodriguez, M. A.; Jimenez-Reyes, P.; Rhea, M. R.; Marin, P. J. (Sports Medicine, 2016)
Volltext siehe: https://www.researchgate.net/publication/292677312